Museum Commemoration Paradigms of Soviet and Soviet Times’ Writers - Keršytė, Nastazija (Bibliotheca Lituana, 2012)
Paper evaluates museum commemoration narratives and paradigms of memory of Soviet Lithuanian writers and writers who lived in Soviet times. Evaluated historical role discourses of these writers suppose museum visualization character and leads to the establishment of or failure to set up writers’ memorial and literature museum. Activation museum visualization, communication is motivated objective writers activity and they creative assessment, prominence of international relations and contexts, and real or seeming relevance of writers at present. The Memorial Museum of writer Antanas Venclova in Vilnius transforming to the Venclovų House-Museum illustrates concepts of discourses about the writer as a Soviet and Soviet times and valuation an artist as beyond Soviet times, Soviet times, and post-soviet times.
Keywords: none